(untitled) (Bulletin of criminological association of Ukraine, 2024)
The scientific article is devoted to the legal regulation of the powers of authorities and local self-government regarding providing rehabilitation assistance to military personnel. The interaction between paramilitary authorities in delivering rehabilitation services to military personnel is analyzed. The legislation consolidating the powers of ministries and services in the medical care field for military personnel is analyzed. It is concluded that the legal regulation of the provision of rehabilitation assistance to military personnel is the consolidation of legal norms in legislative and by-laws, which determine the authority of authorities to manage rehabilitation institutions and establish standards for the provision of rehabilitation services. It is indicated that the tasks of ensuring the implementation of state policy in rehabilitation are assigned to the Cabinet of Ministers of Ukraine. The Ministry of Health of Ukraine wields significant authority in regulating rehabilitation care. It encompasses the approval of legal standards, the implementation of care protocols, and support for sanctioned rehabilitation methods. The role of local self-government bodies in providing rehabilitation services to military personnel is determined. It is emphasized that the Ministry of Defense of Ukraine, the Ministry of Internal Affairs of Ukraine, the State Service for Emergency Situations of Ukraine, and other paramilitary authorities have under their command rehabilitation institutions that can provide rehabilitation services to military personnel. It is established that the order of interaction between paramilitary authorities in providing rehabilitation assistance to military personnel is fixed in by-laws. Proposals are made to improve the legal basis of interaction between the Ministry of Health of Ukraine and paramilitary authorities in providing rehabilitation assistance to military personnel.